2006
DOI: 10.1016/j.ceca.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII inactivation by extracellular Ca2+ depletion in dorsal root ganglion neurons

Abstract: A mechanism by which Ca 2+ /CaM-dependent protein kinase (CaMKII) O has profound effects on intracellular Ca 2+ signaling and CaMKII autophosphorylation, in the absence of measurable changes in intracellular Ca 2+ . These findings have wide-ranging significance, because [Ca 2+ ] O is manipulated in many experimental studies. Moreover, this explanation for the paradoxical changes in CaMKII phosphorylation in response to manipulating [Ca 2+ ] O provides a possible mechanism linking activitydependent depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The rapid chelation of extracellular calcium by BAPTA presumably decreases the amount of calcium in specific intracellular pools that continually drive CaMKII autophosphorylation in the face of significant basal phosphatase activity(ies) that can dephosphorylate Thr286 (Strack et al 1997b, Fukunaga et al 1993, Ishida et al 1998). These findings are consistent with prior studies in cultured neurons showing that removal of extracellular calcium profoundly decreases CaMKII autophosphorylation (Scholz & Palfrey 1998, Cohen & Fields 2006). We also found that extracellular calcium chelation decreases the phosphorylation of GluN2B and GluA1, key synaptic substrates of CaMKII (Hunt & Castillo 2012, Santos et al 2009), suggesting that basal CaMKII activity is driving the phosphorylation of physiological CaMKII substrates.…”
Section: Discussionsupporting
confidence: 93%
“…The rapid chelation of extracellular calcium by BAPTA presumably decreases the amount of calcium in specific intracellular pools that continually drive CaMKII autophosphorylation in the face of significant basal phosphatase activity(ies) that can dephosphorylate Thr286 (Strack et al 1997b, Fukunaga et al 1993, Ishida et al 1998). These findings are consistent with prior studies in cultured neurons showing that removal of extracellular calcium profoundly decreases CaMKII autophosphorylation (Scholz & Palfrey 1998, Cohen & Fields 2006). We also found that extracellular calcium chelation decreases the phosphorylation of GluN2B and GluA1, key synaptic substrates of CaMKII (Hunt & Castillo 2012, Santos et al 2009), suggesting that basal CaMKII activity is driving the phosphorylation of physiological CaMKII substrates.…”
Section: Discussionsupporting
confidence: 93%
“…Rhodamine-conjugated-CGRP-labeled neurons were then processed for immunofluorescence using the anti-TrkB receptor antibody. Control CaMKII immunofluorescence experiments performed on CGRP-treated neurons treated with CaMK inhibitors or incubated for 1 h in Ca 2ϩ -free medium (24) produced no signal (supplemental Fig. 1, A and C).…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously demonstrated in cultured nodose neurons that the CCK-induced increase in cytosolic calcium concentrations is dependent on extracellular calcium influx rather than mobilization on intracellular stores (49). In neurons of the dorsal root ganglia, such a decrease in CaMKII autophosphorylation has been reported in vitro by depleting extracellular calcium (50). The significance of this observation in the present study needs further investigation.…”
Section: Discussionmentioning
confidence: 92%